Wirid Quran Dalam Pengobatan Corona Berbasis Internet - Yaya, Yaya; Tasdik, Komarudin (STAI AL-FALAH CICALENGKA, 2020)
Various solutions have been sought in controlling the Covid-19 pandemic outbreak. Wirid Quran is used as material for treatment, including warding off the Corona outbreak. This study uses descriptive phenomenology and qualitative methods that are correlated with the basic design of an Internet-based (web) expert system. This thesis was once put forward by Qundail which proved that the Quran functions as a medicine in dealing with various diseases. This article proves that the Quran-based treatment for the treatment of Corona patients is still open for further research. Because the method of Internet-based Qur'anic treatment does not reduce the quality of conventional treatment similar. In fact, this approach tends to be easier to create web-based expert systems, so that patients do not need to come directly to the clinic. Keywords: Medicine, Corona, Quran, wirid, Internet Abstrak Berbagai solusi diupayakan dalam pengendalian wabah pandemic Covid-19. Wirid Quran dijadikan materi pengobatan, termasuk menangkal wabah Corona. Penelitian ini menggunakan metode fenomenologi dan kualitatif deskriptif yang dikorelasikan dengan perancangan dasar expert system berbasis Internet (web). Tesis ini pernah dikemukakan oleh Qundail yang membuktikan bahwa Quran berfungsi sebagai obat dalam menghadapi berbagai penyakit. Artikel ini membuktikan bahwa pengobatan berbasis Quran untuk pengobatan pasien Corona masih terbuka untuk dilakukan penelitian lebih lanjut. Karena metode pengobatan Alquran berbasis Internet tidak mengurangi kualitas pengobatan serupa secara konvensional. Bahkan pendekatan tersebut cenderung lebih mudah untuk dibuatkan expert system berbasis web, sehingga pasien tidak perlu datang langsung ke klinik. Kata kunci: Pengobatan, Corona, Quran, wirid, Internet